COGNITIVE MAPS OF EUROPE - Ilkay SUDAS; Cemil GOKTEN (European Journal of Geography)
This paper aims at determining the level of basic geographical knowledge and perspectives of Turkish geography students about Europe, through cognitive maps. R esearch was conducted on a sample of 72 geography undergraduate students from the first and the fourth levels in order to reflect the effect of geographical education on mapping and the ir level of knowledge of Europe. Results indicate that Turkey’s appearance on the cognitive maps is important as it provides us with clues about participants’ thoughts about Turkey’s belonging to Europe and geographical education. For some participants the idea of Europe is formed only within the physical borders and for other participants the idea is linked relatively to economic development and the political context.